The digital SLR guide to the Nikon D80 - Chen, Laurence (Short cut, 2007)
Whether you're thinking about buying or have already purchased a Nikon D80, this 18-page Short Cut guide helps you think about optimizing your digital single-lens reflex camera (DSLR) for various kinds of photographic situations. This guide covers the basic principles to understand how the settings work (alone or in conjunction with other settings) and how to set them for your particular style of shooting. So you know how to go from just "taking a picture" to what professionals refer to as "making a picture." For complete coverage of DSLR cameras and photography, including using Adobe Photoshop to improve your images, try The Digital SLR Guide: Beyond Point-and-Shoot Photography by Jon Canfield. Portraits Landscapes Candid/Sports/Wildlife Macro Photography Conclusion